Factors associated with the presence of acute bacterial prostatitis in patients undergoing transrectal prostate biopsy between 2015 and 2019 at an Armed Forces Hospital in Lima, Peru - Collado-Mendiola, Stefanie (2020)
Objective: to determine the factors associated with the presence of acute bacterial prostatitis in patients undergoing transrectal prostate biopsy between 2015 and 2019 at an Army Forces Hospital in Lima, Peru. Materials and methods: this is a retrospective observational and cross-sectional study. Clinical records from 142 patients were reviewed, which were selected using non-probabilistic sampling. We analyzed factors associated with the occurrence of acute bacterial prostatitis (ABP) in patients undergoing a transrectal prostate biopsy (model 1), and the number of factors associated with ABP (model 2). Results: the rate of ABP was 15.5%. This condition was more prevalent in subjects with diabetes, high blood pressure and chronic renal failure. In model 1, a past history of type 2 diabetes mellitus (aPR: 3.18; 95% CI: 0.92–11.03), high blood pressure (aPR: 1.78; 95% CI: 0.53–5.98), renal failure (aPR: 2.73; 95% CI: 0.60–12.46), and chronic prostatitis (aPR: 4.5; 95% CI: 0.99–20.43) were not associated (p >0.05). In model 2, we found that subjects between 66-75 years of age had a 50% less likelihood for developing APB compared with those in the 50-65 years old group, and that subjects more than 75 years old have a 2.7-fold (95% CI: 0.86–8.13) likelihood for this condition compared with subjects from younger age groups. Finally, it was observed that a greater number of comorbidities increases the likelihood for developing ABP, being this 4.80-fold (95% CI: 1.86–12.42) in those with one concomitant disease, 5.77-fold (95% CI: 1.03–32.13) in those with two concomitant diseases, and 10.47- fold (95% CI: 1.98–55.41) in those who had three concomitant diseases. Conclusions: in this study, a past history of type 2 diabetes mellitus and the number of concomitant chronic conditions increase the likelihood for developing ABP. It is recommended to perform further research on this topic, so our results may be verified.